FIKSASI BAHAN ALAMI BUAH JERUK NIPIS DALAM PROSES PEWARNAAN BATIK DENGAN ZAT WARNA INDIGOSOL - Sri Herlina; S. Eko Putro Widoyoko (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
The research aims to test Calamondin as a natural fixation material in coloring batik using indigosol dyestuff. The tested colors are the oft-used ones, namely Indigosol Yellow IGK, Indigosol Orange HR and Indigosol Blue O₄B. Fixation using HCl commonly used in batik coloring is applied in comparison to these tested colors. The testing comprises color fastness against washing, color fastness against rubbing, and color fastness against sunlight. The assessment standards are grey scale and staining scale. The test result in the laboratory of the Islamic University of Indonesia demonstrates that the values/grades of color fastness against washing, rubbing, and sunlight for most colors are the same as the results of fixation using HC1, and in fact the results of fixation using calamondin for particular colors in particular parameter of color fastness are much better than using HCl. In addition, the values meet the standards of INS (Indonesian National Standard) on batik color fastness. Therefore, calamondin can be used as batik coloring fixation material with indigosol dyestuff which is more environmentally-friendly